Food Intake, Physical Activity and Body Composition of Adolescents and Young Adults: Data from Brazilian Study of Nutrition and Health - De Moraes-Ferrari, G (BioMed Central Ltd, 2021)
Background: Lifestyle acquired in youth can determine the individual’s health. Constant vigilances in all aspects related to the health of the young population is essential, and evaluate their health parameters is important. The objective of this study was to describe and to compare food intake, physical activity (PA) practice, nutritional status and body composition between adolescents and young adults. Methods: Four hundred seventy-six individuals from the Brazilian Study of Nutrition and Health (EBANS) were analyzed. Food intake was evaluated by applying two 24-h Dietary Recall. The PA and sitting time (ST) were measured by the International Physical Activity Questionnaire in minutes/week and metabolic equivalent task (METs). Body weight and waist circumference (WC) were measured. Body mass index (BMI) and waist circumference to height ratio (WHtR) were calculated. Mann-Whitney and Chi-Square tests were used. Results: Energy and macronutrients intake, number of meals, and breakfast skippers weren’t different between age groups. 48% of adolescents and 53% of young adults didn’t meet the PA recommendation, and adolescents practiced more PA than young adults (total PA: p = 0.006; METs: p < 0.001; leisure PA: p = 0.001); the individuals who studied practiced more PA (total PA: p = 0.034; METs: p = 0.029; leisure PA: p < 0.001) and had ST significantly higher (p = 0.009) than those who worked. Almost 30% of adolescents and 45% of young adults had excess weight; presenting difference according to nutritional status, WC and WHtR (p < 0.001). Conclusion: There is a high prevalence of excess weight among young Brazilians and differences were observed between age groups regarding nutritional status, body composition and PA practice. Trial registration: ClinicalTrials.Gov NCT02226627. Retrospectively registered on August 27, 2014. © 2021, The Author(s).